2019
DOI: 10.3389/fnins.2019.01297
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Modifies Noise-Induced Cochlear Injury Related to the Stress Hormone and Autophagy in Female Mice

Abstract: A lack of sleep is linked with a range of inner ear diseases, including hearing loss and tinnitus. Here, we used a mouse model to investigate the effects of sleep deprivation (SD) on noise vulnerability, and explored the mechanisms that might be involved in vitro, focusing particularly corticosterone levels and autophagic flux in cells. Female BALB/c mice were divided into six groups [control, acoustic trauma (AT)-alone, 1 day (d) SD-alone, 1d SD pre-AT, 5d SD-alone, and 5d SD pre-AT]. Cochlear damage was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Female Balb/C mice subjected to sleep deprivation for both one day and segmental five days (sleep deprivation for 22 h and two-hour sleep-free) demonstrated a temporary increase in the amplitude of ABR wave I, but not in the thresholds. The amplitude returned to the baseline level two weeks later [ 34 ]. Male Wistar rats subjected to sleep deprivation for nine days had higher hearing thresholds at 8, 16, and 32 kHz, but not at low frequencies (2–4 kHz).…”
Section: Discussionmentioning
confidence: 99%
“…Female Balb/C mice subjected to sleep deprivation for both one day and segmental five days (sleep deprivation for 22 h and two-hour sleep-free) demonstrated a temporary increase in the amplitude of ABR wave I, but not in the thresholds. The amplitude returned to the baseline level two weeks later [ 34 ]. Male Wistar rats subjected to sleep deprivation for nine days had higher hearing thresholds at 8, 16, and 32 kHz, but not at low frequencies (2–4 kHz).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, as a recently found endogenous self-defense mechanism, degrades damaged organelles by lysosome to maintain internal homeostasis and preserve energy providing for cell survival upon stress like nutrient deficiency, pathogen infection, protein misfolding, and oxidative stress [76][77][78][79][80]. Previous studies [81,82] have shown that autophagy is upregulated in auditory hair cells after 3 Neural Plasticity intense noise exposure. The immunostaining results show the upregulation of LC3b, the indispensable component of autophagosome, and the colocalization of LC3b and Lamp1, indicating the enhanced fusion of autophagosome and lysosome.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, the autophagy induced by short-term SD causes a protective effect on HCs in the apoptotic processes induced by oxidative stress. Thus, it is demonstrated that short-term 3 Neural Plasticity SD exerts protective effects on HCs by regulating corticosterone and activating autophagy after noise exposure [95].…”
Section: Autophagy and Aminoglycoside-induced Hearing Lossmentioning
confidence: 99%
“…The presence of corticosterone receptors in the auditory system has been demonstrated in many studies [ 91 , 92 ], and it has been proved that high levels of corticosterone protect cochlear OHCs from various insults [ 93 , 94 ]. Recently, the effects of SD on noise vulnerability were investigated with respect to the potential underlying mechanisms [ 95 ]. According to the study, the elevated expression of LC3B and autophagy activation is observed in the short-term SD+ acoustic trauma (AT) group, whereas repeated SD+AT group could not exert a similar effect.…”
Section: Autophagy and Hearing Lossmentioning
confidence: 99%